Frants Buhl som gammeltestamentlig teolog - Høgenhaven, Jesper (Dansk Teologisk Tidsskrift, 2015)
Frants Peder William Buhl (1850-1932) is credited with introducing modern critical exegesis in a Danish theological context. This article attempts to track Buhl’s theological concerns. Buhl saw his work as an academic theologian in close connection with the faith and life of the Christian church. In his earlier works he defends a conservative historical position, including a Mosaic origin for Deuteronomy. Later, he embraces basic insights promoted by Julius Wellhausen, and accepts Pentateuchal source criticism and a late date for the Priestly source as founded on valid historical arguments. Buhl retained an independent position with regard to Wellhausen, and remained a great admirer of the conservative scholar Frantz Delitzsch. As a biblical theologian, he worked out a perspective which assigns significant value to the biblical texts as witnesses to a divine revelation unfolding through the course of history, and maintained that historical research at a critical basis is essential to a proper theological understanding of the Old Testament scriptures.